If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5v+19=6(v+12)
We move all terms to the left:
5v+19-(6(v+12))=0
We calculate terms in parentheses: -(6(v+12)), so:We get rid of parentheses
6(v+12)
We multiply parentheses
6v+72
Back to the equation:
-(6v+72)
5v-6v-72+19=0
We add all the numbers together, and all the variables
-1v-53=0
We move all terms containing v to the left, all other terms to the right
-v=53
v=53/-1
v=-53
| 12f+24=-36 | | 12s+24=36 | | -w+1/3+1/2=0 | | 2x/3-3x/5=18 | | 3x+7/4=18 | | 3b=5b-3 | | 9r-7=12 | | 7/10q-3/5=1/15 | | -7t+5=6 | | 6p-7=-2 | | 5^(5x-3)=10 | | 3/4+4x=7/8+6x-6 | | y=57.14(105)+28.57 | | 9+2x=5x-3x+x | | 9+2x=5x-3x+1 | | 9+2x=5x-3x-1 | | b^2+12b+24=7 | | (100/x)+x=0 | | (10x-7)=(7x+11) | | 22x-18=4x | | 22+x-18=4+x | | 0=-16t^2+185 | | 3x/7-14x=5 | | X2-11n+18=0 | | 10.x-60=-200 | | 9^x=195 | | A=30r | | -9/2v-1/5=4/7 | | -4.3+8v=21.3 | | 4+f=15 | | 5o=20 | | s=16(3)^2 |